Are subacromial NSAID injections as effective as subacromial corticosteroid injections for treatment of rotator cuff impingement syndrome?. Issue 6 (June 2018) - Lee, Justin
Abstract : EVIDENCE‐BASED ANSWER : Maybe. In patients with rotator cuff impingement syndrome, a ketorolac injection appears to be superior to a corticosteroid injection for improvement in pain and function (SOR: C, small RCT). A single steroid injection appears to be superior to a single tenoxicam injection, but a series of 3 tenoxicam injections may outperform a single corticosteroid injection (SOR: C, small RCTs).